Pemanfaatan Whatsapp Business dan Instagram Business sebagai media promosi UKM di kelurahan Sialang Sakti - Nur Fitriana; Dewi Clarita; All Ouxtrisa Chandra Mei S (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
WhatsApp Business and Instagram Business are specialized applications of WhatsApp and Instagram, respectively, intended for individuals engaged in business activities. These free-to-download applications serve as valuable tools for promoting products and communicating with potential customers through social media platforms. However, based on information obtained from the Head of RW 03 in Sialang Sakti Village, Tenayan Raya Sub-District, the majority of SME owners in the area lack an understanding of the significance of WhatsApp Business and Instagram Business in fostering business growth. This research aims to provide socialization and training on the utilization of WhatsApp Business and Instagram Business to SME owners. The program was attended by 10 to 15 participants, consisting of SME owners. The methodology involved five stages: preparation of WhatsApp Business material, implementation of WhatsApp Business socialization, preparation of Instagram Business material, implementation of Instagram Business socialization, and training on using both WhatsApp Business and Instagram Business. The research findings indicate that this program has significantly improved SME owners' knowledge regarding promotion on WhatsApp Business and Instagram Business. Consequently, these SME owners are now capable of effectively utilizing these platforms to enhance their sales performance.